A state of art review of peat: geotechnical engineering perspective - Kazemian, Sina; Kim Huat, Bujang; Prasad, Arun; Barghchi, Maassoumeh (Academic Journals, 2011)
Peat is a type of soft soil composed of high contents of fibrous organic matters and is produced by the partial decomposition and disintegration of mosses, sedges, trees, and other plants that grow in marshes and other wet place in the condition of lack of oxygen. These soils are geotechnically problematic as they show high compressibility and low shear strength. In this paper, the origin of peat and its different engineering properties (moisture content, bulk density, specific gravity, void ratio, permeability, compressibility, shear strength) are discussed in the perspective of a geotechnical engineer. The engineering behavior of peat can be improved by chemical stabilization using sodium silicate grout system, cement stabilization, cement stabilized columns, and fiber reinforcement to name a few.